Two Faces of Party Unity: Roll-Call Behavior and Vote Explanations in the German Bundestag. Issue 2 (22nd February 2018) - Zittel, Thomas; Nyhuis, Dominic
Abstract: This article points to vote explanations in the German Bundestag as means to broaden our empirical conception of parliamentary party unity. Vote explanations provide opportunities to take positions on floor votes, independent of vote choices. They thus allow to tap into the level of preference unity compared to the level of behavioural unity. Our analysis shows that German legislators frequently use vote explanations to take individual positions that sometimes involve outright criticism on their parties' stances. Furthermore, it shows that related motivations differ from those that govern behaviour in floor votes. Specifically, electoral incentives to seek personal votes matter more for vote explanations while voting behaviour on the floor is to greater degrees affected by office seeking concerns. The article draws from newly collected data on the 17th Bundestag that includes 274 roll-call votes and also the results of a manual coding of all 1005 unique vote explanations that were tabled in this term.